2 The Statutes at Large, from the Fifteenth Year of King Edward III to the Thirteenth Year of King Hen. IV, inclusive, at 253 (Danby Pickering ed., 1762) - (:unkn) unknown (My University)
Cap. XXIX-Certain Restraints Laid on Wholly Born Welshmen. Passed 1400 (anno secundo Henrici IV): Prohibited Welshmen from bearing any armour with cities, boroughs, or merchant towns. Violators forfeit said armour and imprisoned until a fine is paid on their behalf.
Keywords: CARRY